Hubungan antara skala skor FOUR dan CT Marshall dengan penilaian GCS pada penderita cedera otak akibat trauma - Matoha, Jemmy; Prasetyo, Eko; Oley, Maximillian Ch. (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: Brain injury due to trauma is one of the main causes of deaths among traffic accident cases. This study was aimed to obtain the FOUR score scale and the CT Marshall, as well as to evaluate the relationships between FOUR score scale dan CT Marshall related to GCS in brain injury patients due to trauma. This was a prospective correlation study conducted at the Emergency Unit in Prof. Dr. R. D. Kandou Hospital Manado. There were 58 patients that fulfilled the inclusion criteria, consisted of 41 males (70.7%) and 17 females (29.3%). The correlation test of FOUR score and GCS score showed an X2 value of 77.215 (P < 0.001) meanwhile of the CT Marshall score and GCS score obtained an X2 value of 32.359 (P < 0.001). The correlation between FOUR score and CT Marshall score was tested with Spearman corrrelation test which showed Ï“s= -0.433 (P < 0.001). Conclusion: There was a statistically highly significant strong correlation between FOUR score and GCS score, but a statistically highly significant moderate correlation between CT Marshall and GCS. There was a statistically highly significant negative correlation between FOUR score and CT Marshall score.Keywords: brain injury, trauma, FOUR score scale, CT Marshall, GCSAbstrak: Cedera otak akibat trauma (COT) merupakan salah satu penyebab utama kematian pada kasus-kasus kecelakaan lalu lintas. Penelitian ini bertujuan untuk menilai skala skor FOUR CT Marshall pada penderita cedera otak akibat trauma, dan menilai hubungan antara skala skor FOUR dan CT Marshall dalam menilai GCS pada penderita cedera otak akibat trauma Jenis penelitian ini ialah prospektif dengan pendekatan korelatif yang dilakukan di Intalasi Rawat Darurat Bedah (IRDB) RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian mendapatkan 58 pasien yang memenuhi kriteria inklusi, terdiri dari 41 pasien laki-laki (70,7%) dan 17 pasien perempuan (29,3%). Uji statistik mengenai hubungan antara skor FOUR dan skor GCS (Cedera Kepala) mendapatkan X2 = 77,215 (P < 0,001). Uji statistik mengenai hubungan antara CT Marshall dan skor GCS (cedera kepala) mendapatkan X2 = 32,359 (P < 0,001). Pengujian hubungan skor FOUR dan CT Marshall dengan analisis korelasi Spearman mendapatkan Ï“s= -0,433 (P < 0,001). yang menyatakan terdapat hubungan negatif yang sangat bermakna antara skor FOUR dengan CT Marshall. Simpulan: Terdapat hubungan kuat yang sangat bermakna antara skor FOUR dan GCS serta hubungan sedang yang sangat bermakna antara CT Marshall dan GCS. Terdapat hubungan negatif yang sangat bermakna antara skor FOUR dengan CT Marshall.Kata kunci: cedera otak, trauma, skala skor FOUR, CT Marshall, GCS